PELATIHAN DISAIN WEB BERBASIS HTML 5 DAN SCRIPTING, SERTA PELATIHAN DIGITAL MARKETING KEPADA MASYARAKAT PRA-KERJA DI KOTA MEDAN - Rimbun Siringoringo; Resianta Perangin-angin; Rasmulia Sembiring; Mahendra Tlapta Sitepu; Roni Jhonson Simamora; Jimmy F. Naibaho; Marlyna Infryanty Hutapea; Rena Nainggolan; Eva Julia G. Harianja; Mufria J. Purba; Jepriyanta N. Brahmana; Petty Exclesia Pardosi; Yohana Angelita Manullang (Universitas Methodist Indonesia, 2021)
The aims and objectives of this Community Service are to implement the Tridarma of Higher Education and contribute ideas and transfer technology to the pre-employment force in Medan City. As we all know that the application of information technology, especially websites, has touched all aspects of human life such as business, education, government, health, and other fields. Therefore, skilled personnel is needed in the field of web design in order to meet market needs and employment needs. This community service activity was carried out for fifteen days with training materials on web design and digital marketing. This PkM was carried out in collaboration with partners, namely the Labor Agencies Office of Medan City and with PT. Hagatekno Mediata.